Agricultural Land Protection for Food Security: Policy Integration of Protected Rice Field Map in Spatial Planning in Demak Regency - Kusuma Dewi, Chabibah; Wulansari, Harvini (Marcapada: Jurnal Kebijakan Pertanahan, 2024)
Indonesia is a major agricultural country in Southeast Asia. According to the results of integrated food crop agricultural statistics data gathering operations in 2023, the area designated for rice harvesting is 10.21 million hectares. Indonesia imports rice from numerous nations to address its population's unmet food demands. This rice import activity indicates that Indonesia's food security is not yet fully established. When there was a mismatch between the Protected Rice Fields (LSD) map and the RTRW laws in effect in the region, difficulties emerged. Many lands with spatial designs were classified as LSD. We have yet to completely apply the new agricultural land preservation legislation. This is due to several flaws in the map caused by the determination of protected rice fields. This study intends to determine LSD's position in respect to LP2B, examine the potential impact of map disintegration during policy implementation, and suggest new LSD methods and policies to protect agricultural land through integration with RTRW. This study employs a qualitative research methodology. The conclusions of this study indicate that the LSD policy must immediately improve spatial data; with adequate and accurate spatial data, the LSD policy can be implemented in tandem with other policies. The LSD provided to PSN land suppliers can be replaced with Protected Rice Field Reserve Land, or by identifying locations with surplus food security and putting in place mechanisms to protect rice fields in such regions. The concept entails protecting LSD by securing protected rice field reserve area to preserve its long-term viability, as well as combining the LSD map with the RTRW to allow regional development and expansion.